Hepatic effects of a phthalate ester plasticizer leached from poly(vinyl chloride) blood bags following transfusion. - Kevy, S V (1982)
The effects of di(2-ethylhexyl) phthalate (DEHP) on hepatic function and histology were evaluated in the rhesus monkey undergoing platelet and plasma transfusion. The average cumulative amount infused in one year is comparable to that received by patients who undergo chronic transfusion. Abnormalities in hepatic scan and BSP kinetics persisted for up to 26 months after transfusion, as did histologic abnormalities. Patients undergoing maintenance hemodialysis receive a yearly dose of DEHP which is 10-20 times that which produced hepatotoxicity in the transfused rhesus.